Motivation, Opportunity and Risk-Taking Propensity Influence on LCIs ’ Policy Formulation Ability and Engagement Behaviour: Extension of the MOA Model - Nabafu, Robinah; Isoh, Alain Vilard Ndi; Kituyi, Geoffrey Mayoka; Moya, Musa Bukoma; Ngwa, Oneurine; Mbarika, Victor (University of Dar es Salaam Library Journal, 2023)
Local Council Ones (LC1s) in Uganda are considered key in giving realistic and representative views for policy formulation following their continuous interaction with community members yet their engagement levels are still low. Low engagement in policy formulation could be attributed to limited research done in their context to know what could influence their engagement. This paper examined the role of motivation, opportunity, and risk-taking propensity in improving their ability and engagement behaviour. This study postulated that; motivation, opportunity and risk-taking propensity influence ability and engagement and the relationship between risk-taking propensity and engagement are moderated by gender. A quantitative research method was used to collect data from 185 LCIs in four cities and four districts in Uganda using a survey questionnaire. Validity and reliability of the study instrument was tested using SPSS while structural equation model for testing the formulated hypothesis was designed using SEM. Results reveal that; motivation, opportunity and risk-taking propensity influence ability. Ability, risk-taking propensity and motivation influence engagement while ability partially mediates the relationship between motivation, risk-taking propensity and engagement but fully mediates the relationship between opportunity and engagement. Gender does not moderate the relationship between risk-taking propensity and engagement. This study extended the Motivation, Opportunity, and Ability (MOA) model by adding risk-taking propensity which has a partial influence on engagement. The practical implication is that these findings can be used to improve LC1s ' engagement in policy formulation. Policy formulators should therefore put much emphasis on increasing LCIs ' motivation and risk-taking propensity by considering their views and formulating inclusive and representative policies.